Colonialism and Christianity in Mandate Palestine - Robson, Laura (University of Texas Press, 2021)
Drawing on a rich base of British archival materials, Arabic periodicals, and secondary sources, Colonialism and Christianity in Mandate Palestine brings to light the ways in which the British colonial state in Palestine exacerbated sectarianism. By transforming Muslim, Christian, and Jewish religious identities into legal categories, Laura Robson argues, the British ultimately marginalized Christian communities in Palestine. Robson explores the turning points that developed as a result of such policies, many of which led to permanent changes in the region's political landscapes. Cases include the British refusal to support Arab Christian leadership within Greek-controlled Orthodox churches, attempts to avert involvement from French or Vatican-related groups by sidelining Latin and Eastern Rite Catholics, and interfering with Arab Christians' efforts to cooperate with Muslims in objecting to Zionist expansion. Challenging the widespread but mistaken notion that violent sectarianism was endemic to Palestine, Colonialism and Christianity in Mandate Palestine shows that it was intentionally stoked in the wake of British rule beginning in 1917, with catastrophic effects well into the twenty-first century